PELAKSANAAN PAGANG GADAI BUMNAG CUBADAK SAKATO MENURUT HUKUM EKONOMI SYARIAH - Indah Tri Rahayu; Syukri Iska (Jurnal Integrasi Ilmu Syariah (Jisrah), 2022)
This study examines the implementation of pagang pagang BUMNAG Cubadak Sakato according to Sharia Economic Law. The problem is the implementation of pagang pagang BUMNAG Cubadak Sakato, has a stipulation in paying the debt that the pawner is obliged to give a share of the harvested rice fields obtained by dividing in half between the pawnbroker and BUMNAG outside of wages and repaying the debt according to the ability of the pawner, without any time limit in terms of payment. the payment. However, the profit sharing system established by BUMNAG Cubadak Sakato is not included in the mortgage installments. From these problems, the question arises how to implement pagang pawn in BUMNAG Cubadak Sakato, and how to implement pagang pawn contracts at BUMNAG Cubadak Sakato in terms of profit sharing according to Sharia Economic Law. This research is a field research (field research). Data obtained through interviews and observations. After the data has been collected, it is processed and analyzed in a qualitative descriptive way. This study found that the implementation of the Pagang Gadai contract at BUMNAG Cubadak Sakato in terms of profit sharing carried out between rahin and murtahin (BUMNAG) was not allowed, because it was not in accordance with rahn theory in Sharia Economic Law. The result of pagang pagang in BUMNAG Cubadak Sakato is the emergence of debt contracts, so that the profit sharing obtained from the utilization of accounts payable by BUMNAG is included in the category of usury.